P-031 End artery location of thrombus predicts poor neurological outcome despite successful thrombectomy for anterior circulation stroke. (23rd July 2022) - Eshraghi, S; Saperian, S; Alawieh, A; Howard, B; Grossberg, J; Tong, F; Jabbour, P; Maier, I; Wolfe, S; Rai, A; Starke, R; Gory, B; et al.
Abstract : Background: Despite successful endovascular thrombectomy for acute ischemic stroke, a significant proportion of patients still fail to demonstrate functional independence at 90 days and show fast and early progression of infarct volume after thrombectomy. Several factors have been proposed to influence the fast progression of infarct volume after successful recanalization including collateral score and post-procedural hemorrhage. In this work, we compare clinical and technical outcomes in patients with ICA LVO to those with concurrent MCA and ACA occlusion. Methods: We analyzed vessel-specific outcomes from the prospectively maintained Stroke Thrombectomy and Aneurysm Registry (STAR). We included adult patients undergoing endovascular thrombectomy for acute ischemic stroke from 32 centers in the US and globally between January 2015 and May 2021. Patients were included if the location of thrombus involved the ICA, ICA+MCA, ICA+ACA, or MCA+ACA. Patient demographics, baseline deficits, admission variables, technical and clinical outcomes were reviewed and compared between the ICA group (including ICA+MCA, ICA+ACA) and the MCA+ACA group. Patients with tandem occlusions were not included. The primary outcome measure was modified Rankin Score (mRS) at 90 days dichotomized into good outcome (mRS 0–2) and poor outcome (mRS 3–6). Secondary outcomes included successful recanalization, procedure time, and rates of post-procedural hemorrhage. Results: A total of 2067 patients were included in the study of which 83 patients (4%) had concurrent MCA and ACA thrombus. When comparing admission variables, there were no differences in age, admission NIHSS, comorbidities, onset to groin time, ASPECT scores, or use of IV-tPA between the ICA group and MCA+ACA group (P > 0, 05). On univariate analysis, the median 90-day mRS was significantly higher in the MCA+ACA group compared to ICA group (5 vs. 4, p < 0.05). There was no difference in rate of symptomatic hemorrhage, successful recanalization rate, or procedure time between the two groups (P > 0.05). On multivariate regression baseline covariates, admission deficits, and procedure time, MCA+ACA location was an independent predictor of lower odds of good outcome compared to the ICA group in the full cohort (aOR=0.46, p= 0.018) and in successfully recanalized patients (aOR = 0.47, p = 0.041). On multivariate linear regression, MCA+ACA location was not an independent predictor of longer procedure time compared to the ICA group. Mortality rate was 56% in the MCA+ACA group compared to 31% in the ICA group (P<0.05). Conclusions: Despite similar vascular territories, concurrent occlusion of the MCA and ACA segments results in worse clinical outcomes compared to more proximal ICA occlusion. The likely explanation for fast progression of infarct in the MCA+ACA group is the higher likelihood of end-artery involvement and lower contribution of collateral flow. Reperfusion of both territories; however, does add to the risk of symptomatic post-procedural hemorrhage. Disclosures: S. Eshraghi: None. S. Saperian: None. A. Alawieh: None. B. Howard: None. J. Grossberg: None. F. Tong: None. P. Jabbour: None. I. Maier: None. S. Wolfe: None. A. Rai: None. R. Starke: None. B. Gory: None. M. Psychogios: None. A. Shaaban: None. A. Arthur: None. J. Kim: None. S. Yoshimura: None. P. Kan: None. R. DeLeacy: None. I. Fragata: None. A. Polifka: None. J. Osbun: None. T. Dumont: None. R. Williamson: None. R. Crosa: None. M. Levitt: None. M. Moss: None. W. Casagrande: None. S. Chowdhry: None. C. Cawley: None.